1986
DOI: 10.1177/0730888486013003006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tokenism on Work Alienation among Urban Public School Teachers

Abstract: Existing theories of the effects of relative numbers, and especially tokenism, on worker behaviors and attitudes are reviewed. Despite the absence of specific reference in the literature to worker alienation as an outcome of token status, an argument is presented drawing upon this research tradition and discussions of marginality to link this dependent variable to tokenism. In addition, often neglected status considerations are included to predict directionality in that linkage. Findings suggest that relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…This theory has been tested using various types of occupational groups including nurses and physicians (Floge & Merrill, 1985); auto workers (Gruber & Bjorn, 1988); school teachers (Dworkin, Chafetz, & Dworkin, 1986); actors/actresses (Hinton, Seggar, & Northcott, 1974); Wall street employees (Roth, 2004); coal miners (Hammond & Mahoney, 1983); coaches (Kane & Stangl, 1991); scientists (Shachar, 2000); and fire fighters (Yoder & Aniakudo, 1995, 1997Yoder & Berendsen, 2001). This theory has also been tested using a variety of jobs within the criminal justice system including judicial positions (Allen & Wall, 1987); lawyers (Epstein, 1981); correctional officers (Farnworth, 1992;Jurik, 1988;Wright & Saylor, 1991); and police officers (Archbold & Schulz, 2008;Belknap & Shelley, 1992;Gustafson, 2008;Krimmel & Gormley, 2003;Martin, 1979Martin, , 1980Martin, , 1994TaylorGreene & del Carmen, 2002;Wertsch, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This theory has been tested using various types of occupational groups including nurses and physicians (Floge & Merrill, 1985); auto workers (Gruber & Bjorn, 1988); school teachers (Dworkin, Chafetz, & Dworkin, 1986); actors/actresses (Hinton, Seggar, & Northcott, 1974); Wall street employees (Roth, 2004); coal miners (Hammond & Mahoney, 1983); coaches (Kane & Stangl, 1991); scientists (Shachar, 2000); and fire fighters (Yoder & Aniakudo, 1995, 1997Yoder & Berendsen, 2001). This theory has also been tested using a variety of jobs within the criminal justice system including judicial positions (Allen & Wall, 1987); lawyers (Epstein, 1981); correctional officers (Farnworth, 1992;Jurik, 1988;Wright & Saylor, 1991); and police officers (Archbold & Schulz, 2008;Belknap & Shelley, 1992;Gustafson, 2008;Krimmel & Gormley, 2003;Martin, 1979Martin, , 1980Martin, , 1994TaylorGreene & del Carmen, 2002;Wertsch, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that when they are in the numerical minority in a group, women and people of color experience negative outcomes (e.g., Taylor and Fiske, 1976;Spangler, Gordon, and Pipkin, 1978;Izraeli, 1983;Dworkin, Chafetz, and Dworkin, 1983); others have shown that women and people of color experience more positive outcomes when in the numerical minority (e.g., Harlan and Weiss, 1981;South et al, 1982;Deaux and Ullman, 1983;Toren and Kraus, 1987). Proponents on both sides of the debate tend to agree that increasing the numbers of traditionally underrepresented groups without altering power relations between dominants and subdominants is unlikely to improve the position of those groups substantially (South et al, 1982;Konrad, Winter, and Gutek, 1992).…”
Section: Diversity and Work Group Functioningmentioning
confidence: 99%
“…Second, this study attempts to reconcile certain inconsistent findings of earlier research by asserting that the impact of gender may be contextual. I hypothesize, like several sociologists have for other professions (Dworkin, Chafetz, & Dworkin, 1986;Floge & Merrill, 1986;Kanter, 1977;Yoder, 1991), that women justices may be more willing to express behavioral differences that do exist once the proportion of women extends beyond tokenism. In short, this research taps both of Palmer's (2001) questions by positing that the answer to the first (Does gender matter?)…”
mentioning
confidence: 73%
“…For instance, Dworkin et al (1986) find that female public school teachers became more alienated from their work as their numbers declined. Kanter (1977) argues that it is the rarity of high-level saleswomen, not their gender, that appears to impede their chances of advancement and leads to feelings of isolation.…”
Section: Does the Number Of Female Justices Matter?mentioning
confidence: 99%